SINERGI PEMBELAJARAN NILAI-NILAI KEWARGANEGARAAN DAN KEGIATAN OLAHRAGA BERBASIS MODEL COSPLAY DALAM PEMBENTUKAN KARAKTER SISWA DI MAN 1 BONE - Cheriani; Sofiyan; Iksar, Muhammad; Salsabila, Annisa; Jaya, Riska; Muliya, Suci; Sulpadli, Muh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the role of citizenship learning and sports coaching activities in fostering student character development at MAN 1 Bone. Using a qualitative descriptive approach, data were collected through observations, interviews, and documentation involving 50 students, teachers, and coaches. The findings indicate that classroom learning promotes discipline, responsibility, and patriotism, while sports coaching strengthens teamwork, resilience, and leadership through structured training. The synergy between both creates a holistic character-building environment, reflected in improved behavior and social responsibility. This integration can be further enhanced through a cosplay-based learning model as a role-play approach to internalize character values. Despite challenges such as limited facilities, the program demonstrates an effective model for character education in madrasahs.